Making All Voices Count: A Slam Dunk? - and Global Integrity (2012)
Yesterday, I had the chance to attend the public launch of a new government transparency and accountability funding mechanism – Making All Voices Count. Held at USAID headquarters, the discussion featured a veritable who’s who of open government and transparency practitioners in the Washington area; probably 250 people were packed into the room. (Announcing a …